Pembentukan saiz pakaian kanak-kanak pra sekolah - Bari, Siti Balkis; Mohd Salleh, Naimah; Sulaiman, Norhasmah; Othman, Mumtazah (Kementerian Pendidikan Malaysia, 2013)
Anthropometric data plays an important role in creating garment sizing system.This study exmined anthropometrydata of children in Malaysia in order to develop a garment sizing system. The study involves 216 pre school students rural and urban aged 5 and 6 years old. Data were analysed using SPSS program to get mean and standard deviation. Using Beazley formula (1997), three size groups were found. These three different body types were established among the respondents which is the small, regular, and big size. A body sizing system based on the key dimension is developed by suggesting from Aldrich (1999). Finally, a sizing system to cover garment for pre school students was developed. This research finding will give the right garment sizing to the pre school students.